Survival of Shiga Toxin-producing Escherichia coli (O157:H7 and Non-O157:H7) and Effectiveness of Thermal Inactivation by Microwaves in Nham (Thai Fermented Sausage) - Chantarapanont, Walairut; Nitisinprasert, Sunee; Frank, Joseph F. (Agriculture and Natural Resources, 2012)
A study was conducted to determine if the fermentation conditions of Nham (Thai fermented sausage) were effective against Escherichia coli O157:H7 and three non-O157:H7 Shiga toxin-producing E. coli, O8 (stx2+, eaeA-), O111 (stx1+, eaeA+) and untypable O serogroup (stx1+, eaeA-) strain, compared with non pathogenic E. coli, E780 as a negative control. Nham was produced using starter cultures of V3 (Pediococcus acidilactici and Staphylococcus xylosus). The pH of Nham during the ﬁ rst 3 d of Nham fermentation was reduced from 6.39 to 4.55. Each of the ﬁ ve strains of E. coli were separately inoculated to unfermented Nham giving initial populations of approximately 2 × 106 colony forming units (CFU).g-1 and fermented at 35 °C for 3 d and stored at 4 °C for up to 20 d after that. All strains except O157:H7 were increased by 1 log CFU.g-1 for the ﬁ rst day of fermentation and decreased by 1 to 2 log CFU.g-1 after Nham fermentation for 3 d. After storing inoculated Nham at 4 °C, the three strains of non-O157:H7 slowly decreased by only 0.5–1 log CFU.g-1 until 20 d of storage at 4 °C. The effectiveness of thermal activation was determined using a capillary tube method. The decimal reduction time (D) values at 58 °C in acidiﬁ ed tryptic soy broth (TSB, pH 4.6) of all strains of nonacid-adapted E. coli (TSB) were higher than for the acid-adapted E. coli (TSB pH 5.8). Nonacid-adapted and acidadapted E. coli O111 showed the highest D values (3.31 and 1.23 min, respectively) at 58 °C while nonacid-adapted and acid-adapted E. coli O157:H7 showed the lowest D values (1.96 and 0.37 min, respectively). The results showed that heating by 900 W microwaves at initial temperatures of 28 °C for 60 s could not destroy any Shiga toxin-producing E. coli (approximately 1 × 105 CFU.g-1) in Nham. E. coli O157:H7 could be destroyed after heating with microwaves for up to 90 s but not all E. coli O111 were. Microwaving Nham might not be a safe way of cooking Nham as some E. coli can survive.